Reduced CA2–CA3 Hippocampal Subfield Volume Is Related to Depression and Normalized by l-DOPA in Newly Diagnosed Parkinson’s Disease - Györfi, Orsolya; Nagy, Helga; Bokor, Magdolna; Moustafa, Ahmed A.; Rosenzweig, Ivana; Kelemen, Oguz; Kéri, Szabolcs (Frontiers in Neurology, 2017)
Hippocampal dysfunctions may play an important role in the non-motor aspects of Parkinson’s disease (PD), including depressive and cognitive symptoms. Fine structural alterations of the hippocampus and its relationship with symptoms and medication effects are unknown in newly diagnosed PD. We measured the volume of hippocampal subfields in 35 drug-naïve, newly diagnosed PD patients without cognitive impairment and 30 matched healthy control individuals. Assessments were performed when the patients did not receive medications and after a 24-week period of L-DOPA treatment. We obtained a T1-weighted 3D-MPRAGE image at each assessment. FreeSurfer v6.0 was used for image analysis. Results revealed selectively decreased CA2-CA3 volumes in non-medicated PD patients, which was normalized after the 24-week treatment period. Higher depressive symptoms were associated with smaller CA2-CA3 volumes. These results indicate that the CA2-CA3 subfield is structurally affected in the earliest stage of PD in the absence of cognitive impairment. This structural anomaly, normalized by L-DOPA, is related to depressive non-motor symptoms.